2019
DOI: 10.3390/app10010092
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Polycyclic Aromatic Hydrocarbons in Traditional Dry Cured Smoked Ham Slavonska Šunka

Abstract: Slavonska šunka is a traditional dry-cured smoked ham. Smoking with open fire commonly results in the accumulation of polycyclic aromatic hydrocarbons (PAH) molecules in tissues. The objective of this research was to assess the types and concentrations of 16 PAHs in 30 samples of traditional dry-cured smoked ham Slavonska šunka. In general, all samples had high values of anthracene while higher levels of acenaphthylene were present in some samples. In sample SS1, the maximal value for anthracene reached 228.03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Other analyzed samples had acceptable values for BaP content. Average levels of BaP were below those reported by other authors [17,30] and in agreement with those reported by Poljanec et al [28] and Bogdanović et al [29] in different types of Croatian prosciuttos. On the other hand, Mastanjević and al.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Other analyzed samples had acceptable values for BaP content. Average levels of BaP were below those reported by other authors [17,30] and in agreement with those reported by Poljanec et al [28] and Bogdanović et al [29] in different types of Croatian prosciuttos. On the other hand, Mastanjević and al.…”
Section: Resultssupporting
confidence: 92%
“…The two substances Ane and Pyr were not detected. Examination results showing the domination of light PAHs was is in agreement with earlier studies on PAHs contaminations in smoked meat products [17,[25][26][27]. Content of light PAHs determined in Hercegovački pršut involved Nap, Anl, Flu, Ant, Phen, Flt, and BaA.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations